2008
DOI: 10.1111/j.1365-2265.2008.03299.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant LH (lutropin alfa) for the treatment of hypogonadotrophic women with profound LH deficiency: a randomized, double‐blind, placebo‐controlled, proof‐of‐efficacy study

Abstract: Subcutaneous co-administration of 75 IU lutropin alfa with follitropin alfa is safe and effective in inducing follicular development in women with profound gonadotrophin deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 62 publications
1
55
0
1
Order By: Relevance
“…Ovulation can be achieved either with pulsatile GnRH therapy [222][223][224] or, alternatively, with FSH treatment followed by hCG or LH to trigger ovulation. 225 One caveat is that most women with CHH do not secrete endogenous LH and, thus, require a complement of LH to stimulate local production of androgen substrates by theca cells, which facilitates sufficient secretion of estradiol by the dominant follicle. [226][227][228] Physiologic estradiol secretion promotes optimal endometrial development and the cervical mucus production needed for sperm transit and embryo implantation.…”
Section: Induction Of Female Sexual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovulation can be achieved either with pulsatile GnRH therapy [222][223][224] or, alternatively, with FSH treatment followed by hCG or LH to trigger ovulation. 225 One caveat is that most women with CHH do not secrete endogenous LH and, thus, require a complement of LH to stimulate local production of androgen substrates by theca cells, which facilitates sufficient secretion of estradiol by the dominant follicle. [226][227][228] Physiologic estradiol secretion promotes optimal endometrial development and the cervical mucus production needed for sperm transit and embryo implantation.…”
Section: Induction Of Female Sexual Characteristicsmentioning
confidence: 99%
“…229 Typically, subcutaneous FSH doses of 75-150 IU per day are sufficient. [223][224][225]229 The usual time required to obtain a dominant mature follicle (>18 mm) is ~12 days. [223][224][225]229 The starting dose of FSH is often increased or decreased depending on the ovarian response, as assessed by repeated serum estradiol measurements or by counting maturing follicles (using ultrasonography) performed approximately every 3-4 days.…”
Section: Induction Of Female Sexual Characteristicsmentioning
confidence: 99%
“…The role of exogenous LH in hypogonadotrophic hypogonadism patients has been shown in many trials [11][12][13][14] whereas the efficacy of this stimulation protocol in other populations such as poor responders is somewhat undetermined. A recent study reported that a certain group of infertile women such as older women might benefit from LH supplementation [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the LH level in the GnRH antagonist protocol decreases (Duijkers et al, 1998;Griesinger et al, 2010) and this may negatively affect implantation or pregnancy rate (Esposito et al, 2001). LH secretion is necessary for appropriate follicular and endometrial development (Shoham et al, 2008;Kaufmann et al, 2007).…”
Section: Low Dose Hcg Administration In Conjunction With Gnrh Antagonmentioning
confidence: 99%